Magmatic, Metamorphic and Structural History of the Variscan Lizard Ophiolite, Cornwall, UK, and its Metamorphic Sole - MacKay-Champion, T; Searle, M (University of Oxford, 2022)
Data contains field observations (lineations, foliations), XRF data, electron-microprobe analysis data, Laser Ablation U-Pb data, and CA-ID-TIMS data. Data collected between 2019 - 2021. No specific software is necessary.